REDUCTION NATURAL REGENERATION DENSITY OF Pinus elliottii BY MANUAL AND MECHANIZED MOWING - Messias Júnior, João Osvani; da Silva, Samuel Alves; Pelissari, Allan Libanio; Nakajima, Nelson Yoshihiro (Floresta, 2020)
The methods of conducting the natural regeneration of Pinus elliottii are alternatives to planting with seedlings, where manual or mechanized mowing is carried out to reduce competition (density), while selective thinning is applied to select the most promising individuals. Thus, this study aimed to compare methods of conducting the natural regeneration of Pinus elliottii based on forest biometric variables: tree density ( ), basal area ( ), injuries to the remaining trees ( ) and production cost. For this, 19 circular plots of 380 m² were allocated in an experimental area of manual mowing with 22.5 ha and 6 plots in a mechanized mowing area with 7.2 ha. The Mann-Whitney test for independent samples was used to verify the existence of statistical difference between the discrete variables N and I , while the test t of Student de two samples, assuming different variances, were applied to the continuous variable G, both at the level of 5% significance. With of 2,012 trees/ha and of 4.07 m²/ha, mechanized mowing was more effective in controlling regeneration. No statistical difference was found between the methods referring to I, while the production cost of manual mowing was 51.7% higher. Thus, it is concluded that the method with mechanized mowing is the most suitable for conducting the natural regeneration of Pinus elliottii.